PERSEPSI PENGUSAHA MANGAT CATERING TERHADAP PERBANKAN SYARIAH - Mawaddah Irham (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2020)
Perception is the process of someone's interpretation of their environment. The purpose of this study was to determine the perceptions of catering mangat entrepreneurs towards Islamic banking in the city of Medan. The method used is a qualitative method with interviews. The results of this study are; The perception of the catering spirit entrepreneur towards Islamic banking is good. According to him, Islamic banks with the concept of sharing the results, are free from usury and can help customers to transact in a halal manner. So that customers feel safe and comfortable as well as blessings in transactions. The experience of catering entrepreneurs in using sharia banking services, namely that there are many conveniences in business activities carried out, for example in transfer transactions, the service is quite easy and reaches the intended account as well as when receiving transfers from consumers, immediately receiving notifications via messag services on cellphones . During the use of Islamic banking services, there were no obstacles or obstacles experienced, and it went well, as well as catering entrepreneurs who felt helped by the existence of Islamic banking services